Charity and Truth, Truth and reason, Truth and development, Knowledge of God, Onto-theology - Arellano Cruz, Martha (2010)
This paper tries to put on the table some important aspects –from the perspective of social sciences –on comprehensive human development by trying to answer the following questions: Why and for what is important to under stand such concept? Why want and hunger continues to strike around the world? To answer these questions, the interpretations on comprehensive human development havebeen described in two parts: the first is how Caritas in Veritate understands this concept, and the second are the UNDP contributions to development.